2018
DOI: 10.1177/1010428318811525
|View full text |Cite
|
Sign up to set email alerts
|

Cell-adhesion molecules and their soluble forms: Promising predictors of “tumor progression” and relapse in leukemia

Abstract: Some surface markers are used to discriminate certain leukemic subpopulations that retain a greater oncogenic potential than others, and, for this reason, they were termed as leukemic stem cells, similar to the concept of cancer stem cells in carcinoma. Among these surface markers are proteins involved in cell-cell adhesion or cell-matrix adhesion, and they may play a role in the relapse of leukemia, similar to metastasis in carcinomas. The most important are epithelial cadherin, neural cadherin, epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 103 publications
(216 reference statements)
0
17
1
Order By: Relevance
“…Cadherin adhesion molecules are core components in adherens junctions, located on the basement membrane aspect of polarized epithelial cells. E-cadherin, specifically, is a calcium-dependent adhesion integrin that is abundant in epithelial tissues and plays an important role in cell–cell adhesion complexes including desmosomes and adherens junctions [12]. In our study, we found significantly increased expression of E-cadherin in cells that stably or transiently expressed HBV, which is inconsistent with studies that have reported that hepatitis B virus X protein (HBx) represses E-cadherin expression [13].…”
Section: Introductioncontrasting
confidence: 99%
“…Cadherin adhesion molecules are core components in adherens junctions, located on the basement membrane aspect of polarized epithelial cells. E-cadherin, specifically, is a calcium-dependent adhesion integrin that is abundant in epithelial tissues and plays an important role in cell–cell adhesion complexes including desmosomes and adherens junctions [12]. In our study, we found significantly increased expression of E-cadherin in cells that stably or transiently expressed HBV, which is inconsistent with studies that have reported that hepatitis B virus X protein (HBx) represses E-cadherin expression [13].…”
Section: Introductioncontrasting
confidence: 99%
“…In the context of CAMs, circulation of soluble extracellular domains is often associated with inflammatory states. Their serum levels are increased in cardiovascular disorders such as arteriosclerosis and in some forms of cancer (69). Moreover, they can be found in acute disseminated encephalomyelitis, which is a postinfectious inflammatory disease, and in the serum and cerebrospinal fluid (CSF) of patients with multiple sclerosis, where their level correlates with disease severity (70).…”
Section: Discussionmentioning
confidence: 99%
“…Cadherin adhesion molecules are core components in adherens junctions, located on the basement membrane aspect of polarized epithelial cells. E-cadherin is a calcium-dependent adhesion integrin that is abundant in epithelial tissues and plays an important role in cell-cell adhesion complexes including desmosomes and adherens junctions (Fonseca et al, 2018). Ecadherin play a role in pathogen infection (Bonazzi and Cossart, 2011).…”
Section: Introductionmentioning
confidence: 99%